Microinnovations for organizational sustainability: small actions, big impacts - Ordoñez Iturralde, Darwin Daniel (Universidad Francisco de Paula Santander, 2025)
This study examines how microinnovations—small, low-cost actions—contribute to organizational sustainability. Based on a theoretical review, three approaches are identified: operational, cultural-organizational, and user-oriented. Their flexibility, replicability, and ability to generate cumulative impact are highlighted, especially in SMEs or resource-limited contexts. The findings underscore their strategic value and the need to develop specific indicators that enable their effective measurement and scaling.